Proceedings of the 8th International Conference on Knowledge Capture 2015
DOI: 10.1145/2815833.2815845
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Prominent Life Events on Twitter

Abstract: Social media is a common place for people to post and share digital reflections of their life events, including major events such as getting married, having children, graduating, etc. Although the creation of such posts is straightforward, the identification of events on online media remains a challenge. Much research in recent years focused on extracting major events from Twitter, such as earthquakes, storms, and floods. This paper however, targets the automatic detection of personal life events, focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…• LR (TFIDF) (Dickinson et al 2015): The researchers use TF-IDF vectors as the representations of news articles and employs Logistic Regression as the classifier for a PRED task. We directly adopt it in our experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• LR (TFIDF) (Dickinson et al 2015): The researchers use TF-IDF vectors as the representations of news articles and employs Logistic Regression as the classifier for a PRED task. We directly adopt it in our experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 Besides the current task, textual descriptions are also utilized in solving detection problems, with the most relevant one being Person-Related Event Detection (PRED). Instead of mining public news reports on celebrities, PRED aims to detect predefined personal life events from social media by classifying user-posted text, especially tweets, into categories such as having children (Dickinson et al 2015) or visiting (Yen, Huang, and Chen 2019). Though we can also model our task by classifying the aforementioned candidate locations into positives (actually visited) and negatives (actually not visited) given their textual contexts, adopting the PRED methods can be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Other works use keywords to gather a life event themed corpus, crowdsourcing to annotate it, and then use the annotated data to build a model that can automatically associate tweets with a life event. Dickinson et al [10], focused on five life events psychologists have identified to be the most prominent in peoples' lives: "Starting School", "Falling in Love", "Getting Married", "Having Children", and "Death of a Parent". They were able to use the content features of tweets such as n-grams, mentions, and number of retweets, user, semantic, and interaction features to build an effective classifier using labeled data from crowdsourcing.…”
Section: Detecting and Inferring Life Eventsmentioning
confidence: 99%
“…Event detection from social media has received considerable attention, in particular, pinpointing important life events (Li et al, 2014;Dickinson et al, 2015). Previous research shows that people often tweet about events they do not participate in (Sanagavarapu et al, 2017), targets recurring events (Kunneman and Van den Bosch, 2015), and summarizes tweet streams about TV shows (Andy et al, 2019).…”
Section: Previous Workmentioning
confidence: 99%